Internationalizing early childhood curriculum foundations of global competence - Brown, Nancy 1951- (New York Routledge, 2019)
"Internationalizing Early Childhood Curriculum empowers teachers and directors to internationalize their curriculums around the world in their own unique and culturally specific ways. Serving as a guide and catalyst for thinking about curriculum in our interconnected world, this book explores how young children learn about the world and describes how children develop intercultural understanding, including how their teachers transform to expand their own global awareness and citizenship. Stories from actual classroom curriculum projects are featured, as well as suggested strategies and stages for the process of implementation. Exploring the implications for teacher education and professional development, this book gives readers the tools they need to bring internationalization into their own programs. Designed to apply to formal and informal early childhood centers across the spectrum, Internationalizing Early Childhood Curriculum is essential reading for professional developers and trainers, as well as classroom teachers, directors, policy-makers and NGO professionals providing early childhood services in the U.S. and around the world"--Provided by publisher.
Why international? Why now? A theoretical rationale -- Guidelines for internationalizing early childhood curriculum -- Stories from the classrooms -- Transformational portraits : the teachers -- Children's voices and artistic expressions -- Conclusions, recommendations and reflections.
Includes bibliographical references (pages [129]-138) and index.
Keywords: Early childhood education -- Curricula; International education; Curriculum planning